Nd2007 2007
DOI: 10.1051/ndata:07364
|View full text |Cite
|
Sign up to set email alerts
|

A new high efficiency array of C6D6 detectors for capture cross section measurements at GELINA

Abstract: Abstract. Neutron capture cross section measurements at the Geel Electron Linear Accelerator (GELINA) rely on the use of H-free deuterated benzene C 6 D 6 liquid scintillators. A new design of Aluminium canned C 6 D 6 detectors was studied to improve the performances (high gamma efficiency vs. low neutron sensitivity) of the cylindrical previous ones: on the basis of a truncated 5-sides pyramid, the new detectors were developed and tested in Geel, and used in a preliminary capture cross section measurement on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Borella et al [9] and Sage et al [8] reported on the response functions of the C 6 D 6 detectors that are used for capture cross-section measurements at GELINA with the conventional acquisition system. Many authors already demonstrated that reliable detector responses can be calculated by Monte Carlo simulations, provided that the geometry input file reflects the measurement conditions and the light output function and resolution are defined.…”
Section: Pulse Height Linearity and Resolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Borella et al [9] and Sage et al [8] reported on the response functions of the C 6 D 6 detectors that are used for capture cross-section measurements at GELINA with the conventional acquisition system. Many authors already demonstrated that reliable detector responses can be calculated by Monte Carlo simulations, provided that the geometry input file reflects the measurement conditions and the light output function and resolution are defined.…”
Section: Pulse Height Linearity and Resolutionmentioning
confidence: 99%
“…In Refs. [8,9] the quality of response functions obtained by Monte Carlo simulations, using the MCNP code, is discussed by comparison with experimental response functions for quasi-mono-energetic gamma-ray sources.…”
Section: Pulse Height Linearity and Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 12.38 m station a new system of ten large C 6 D 6 scintillation detectors [7] arranged in a dodecaeder configuration has been installed. To determine the elemental composition at different places of the object, the sword was placed in an automated scanning system, which was linked to the data acquisition system.…”
Section: Experiments At Gelinamentioning
confidence: 99%